2018
DOI: 10.1080/10803548.2018.1429079
|View full text |Cite
|
Sign up to set email alerts
|

Violence breeds violence: burnout as a mediator between patient violence and nurse violence

Abstract: The present study examines whether patient-perpetrated violence triggers anger, hatred and other negative emotions that, under certain circumstances, might motivate nurses to behave violently with patients. In doing so, this study considers burnout as a mediator in the patient violence-nurse violence relationship. To test the causal paths, data were collected from 182 nurses working in two government-sector teaching hospitals of Pakistan's Punjab province. Results confirm that patient violence toward nurses le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
1
25
0
1
Order By: Relevance
“…Workplace incivility has been hypothesized as having a negative connection to job satisfaction (e.g., Cortina, Kabat‐Farr, Leskinen, Huerta, & Magley, ). Such behavior has been shown to have a significant impact on job satisfaction among nurses (Guidroz, Burnfield‐Geimer, Clark, Schwetschenau, & Jex, ), leading to job dissatisfaction and increased turnover among nurses in Pakistan (Laeeque, Bilal, Hafeez, & Khan, ).…”
Section: The Impact Of Incivilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Workplace incivility has been hypothesized as having a negative connection to job satisfaction (e.g., Cortina, Kabat‐Farr, Leskinen, Huerta, & Magley, ). Such behavior has been shown to have a significant impact on job satisfaction among nurses (Guidroz, Burnfield‐Geimer, Clark, Schwetschenau, & Jex, ), leading to job dissatisfaction and increased turnover among nurses in Pakistan (Laeeque, Bilal, Hafeez, & Khan, ).…”
Section: The Impact Of Incivilitymentioning
confidence: 99%
“…Although an environment of incivility has been shown to have a negative effect on nurses and their patients (Smith, Morin, & Lake, ) and to lower job satisfaction among nurses in public hospitals (Laeeque et al, ), some studies have revealed no significant effect of workplace incivility on job satisfaction in other environments (Alola, Olugbade, Avci, & Öztüren, ; Cingöz & Kaplan, ; Walker, ). Little on this subject has been explored from the Asian perspective (Ghosh, ).…”
Section: The Impact Of Incivilitymentioning
confidence: 99%
“…Daily, they endure fatigue, frustration, and with patients while providing services [4], which increases burnout. To make matters worse, tired doctors can easily trigger further negative outcomes, [2,5,6] such as deterioration of doctor-patient relationships [7] and escalated violence in the health care sector [7]. Therefore, it is understandable that professional burnout among doctors has drawn continuous attention among academics and the public worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Singapore (Lim & Teo 2009); but also affected the local context healthcare sector nurses in Pakistan (Ziaud-Din, Arif & Shabbir, 2017). The worsening situation due to lack of government attention (Basharat, 2017) is consequently dampening job satisfaction among public hospital nurses in Pakistan (Laeeque, et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%